PRODUCTIVE REGIONAL CONCENTRATION IN THE STATE OF PARANÁ: CASE STUDY OF NON-WOOD FOREST PRODUCTS - Corrêa Bittencourt, Keila; de Paula, Thiago Rodrigues; Juazeiro dos Santos, Anadalvo; Tuyoshi Hosokawa, Roberto; Hoeflich, Vitor Afonso (Floresta, 2019)
The non-wood forest products (NWFPs) have significant productive potential in the State of Paraná, Brazil. In this paper we analyzed the five NWFPs most representative in the state:. Yerba mate, Palmito (Pupunha, Juçara and Real), Pinion, Resin and Latex. The results showed that although many municipalities participate at some level in their production, there are concentration when analyzing the Paraná mesoregions. That is, there is a concentration of production in the middle region west andsoutheast to the Yerba Mate, in the Curitiba metropolitan middle region for the production of Palmito and all mesoregions have a significant production of pinion. The Curitiba metropolitan mesoregion participates with most of theproduction of resin and mesoregion Northwest with the highest production of latex. The importance of the study comes of the lack of public policies to assist, direct and oversee the production and marketing of NWFPs, which generates a suboptimal result from the point of sustenaible develompment. In conclusion it has to be a regional analysis using Quotient Locational, both for production and for the production value, has proved a valuable tool to characterize the Paraná mesoregions about their participation in the production of non wood forest products in the State of Paraná and to identify the productive potential of NWFPs. Thus, current and future actions os state government and all other stakeholders in order development regional into may make use of this analysis as part of its planning, in order to allow society to benefit from the development of NWFPs in the state.